2017
DOI: 10.1371/journal.ppat.1006092
|View full text |Cite|
|
Sign up to set email alerts
|

The TIR Homologue Lies near Resistance Genes in Staphylococcus aureus, Coupling Modulation of Virulence and Antimicrobial Susceptibility

Abstract: Toll/interleukin-1 receptor (TIR) domains in Toll-like receptors are essential for initiating and propagating the eukaryotic innate immune signaling cascade. Here, we investigate TirS, a Staphylococcus aureus TIR mimic that is part of a novel bacterial invasion mechanism. Its ectopic expression in eukaryotic cells inhibited TLR signaling, downregulating the NF-kB pathway through inhibition of TLR2, TLR4, TLR5, and TLR9. Skin lesions induced by the S. aureus knockout tirS mutant increased in a mouse model compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…Expression of the TIR domain alone (BtpB-TIR) resulted in the formation of long filament-like structures that showed no colocalization with tubulin ( Fig 6), consistent with the results obtained in the yeast model. In some cells, BtpB-TIR induced disorganization of the microtubule network ( what has been previously described for the Staphyloccocus aureus TirS protein [7]. Most likely, as also inferred from the above yeast data, these structures correspond to self-assembled ordered filaments consisting of the TIR domain, which are absent when stabilized by the presence of the N-terminal domain.…”
Section: Inhibition Of Endocytosis Occurs Upon Ectopic Expression Ofsupporting
confidence: 71%
See 1 more Smart Citation
“…Expression of the TIR domain alone (BtpB-TIR) resulted in the formation of long filament-like structures that showed no colocalization with tubulin ( Fig 6), consistent with the results obtained in the yeast model. In some cells, BtpB-TIR induced disorganization of the microtubule network ( what has been previously described for the Staphyloccocus aureus TirS protein [7]. Most likely, as also inferred from the above yeast data, these structures correspond to self-assembled ordered filaments consisting of the TIR domain, which are absent when stabilized by the presence of the N-terminal domain.…”
Section: Inhibition Of Endocytosis Occurs Upon Ectopic Expression Ofsupporting
confidence: 71%
“…TcpC inhibition of TRIF-and IL-6/IL-1-dependent pathways has also been described [6]. Interestingly, the observation that expression of TirS from Staphylococcus aureus, present in a multi-drug resistant (MDR) island of numerous clinical isolates, is induced by specific antibiotic treatment [7] raises the possibility that these bacterial proteins may be tightly regulated, enhancing virulence, persistence or dissemination in particular clinical contexts such as exposure to selective pressure.…”
Section: Introductionmentioning
confidence: 92%
“…In some cells, BtpB-TIR induced disorganization of the microtubule network (S5C Fig). These filamentous structures did not co-localize with vimentin either, a marker of intermediate filaments (S5D Fig), strongly reminiscent of what has been previously described for the Staphyloccocus aureus TirS protein [7]. Most likely, as also inferred from the above yeast data, these structures correspond to self-assembled ordered filaments consisting of the TIR domain, which are absent when stabilized by the presence of the N-terminal domain.…”
Section: Resultssupporting
confidence: 79%
“…First, prior work from our laboratory in a mouse model of S. aureus catheterassociated biofilm infection also demonstrated a TLR9independent phenotype [22], confirming the findings obtained during craniotomy infection. Second, as previously mentioned, numerous S. aureus virulence determinants have recently been identified that interfere with TLR2 recognition or signaling [46][47][48][49]; however, to date, no S. aureus inhibitors of TLR9-dependent pathways have been reported. By extension, this suggests that TLR2-mediated recognition of S. aureus is more relevant for bacterial clearance, since this pathway has been extensively targeted by the organism.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is critical for S. aureus containment during craniotomy infection, but is not sufficient for bacterial clearance, since biofilm infections persist in an immune competent host during craniotomy infection. Prior studies have identified several molecules that are produced by planktonic S. aureus that interfere with TLR2-dependent recognition, including lipase (Geh) [46], staphylococcal superantigenlike protein 3 (SSL3) [47], and molecular mimicry via blocking the Toll-interacting receptor (Tir) domain of TLR2 [48,49]. In addition, the paired-immunoglobulinlike receptor (PIR)-B contains an inhibitory immunoreceptor tyrosine-based inhibition (ITIM) motif that upon binding S. aureus lipoteichoic acid, dampens proinflammatory cytokine production [50,51].…”
Section: Discussionmentioning
confidence: 99%